Design and experiment of the environment control system for the industrialized production of Agaricus bisporus - Zhao, Kaixuan; Zhu, Xuefeng; Ma, Hao; Ji, Jiangtao; Jin, Xin; Sun, Jingwei (International Journal of Agricultural and Biological Engineering, 2021)
Environment parameters are the main factors affecting the growth and development of Agaricus bisporus. Because of the requirements of environmental conditions for high-efficiency industrialized production of Agaricus bisporus, equipments for environment control were developed. Based on the variable operating equipment, a multi-factor fuzzy controller was designed to realize the comprehensive control of ambient temperature, humidity, CO2 concentration, and the temperature and moisture of the compost. The test results showed that the temperature control error was less than ±0.5°C and the response speed was more than 0.5°C/h; The control error of ambient humidity was less than ±2% RH, and the response speed was more than 9% RH per hour; The moistures at different points in compost ranged from 50% to 70% with a standard deviation of 4.04. The control accuracy of environmental CO2 concentration was within 200 µmol/mol. The overall performance of the control system was stable and reliable, which could meet the requirements of environment factors for the growth of Agaricus bisporus. The system can provide technical support and reference for the automatic and precise control of the environment during the industrialized production of Agaricus bisporus.Keywords: environment control system, Agaricus bisporus, industrialized production, vertical agriculture, fuzzy controller, design, experimentDOI: 10.25165/j.ijabe.20211401.5635Citation: Zhao K X, Zhu X F, Ma H, Ji J T, Jin X, Sun J W. Design and experiment of the environment control system for the industrialized production of Agaricus bisporus. Int J Agric & Biol Eng, 2021; 14(1): 97–107.